Transforming neonatal nursing in India: challenges, opportunities, and the way forward - Geetanjali Kalyan; Poonam Joshi; Lumchio Levis Murry; Marsha Campbell-Yeo; Surya Kant Tiwari (The Lancet Regional Health - Southeast Asia)
Summary: Neonatal care is essential for the well-being of newborns, particularly premature or critically ill patients. Despite advancements in medical technology and evidence-based practice, India faces significant challenges in neonatal nursing, including resource limitations, inconsistent training, and inadequate policy support. This paper examines the current state of neonatal nursing in India, highlighting disparities between urban and rural areas, and comparing them to global practices. It explores systemic issues affecting neonatal care, such as inadequate educational frameworks, a shortage of trained faculty, and insufficient clinical exposure. We outline a comprehensive approach to address these challenges, including the introduction of Neonatal Nurse Practitioner programs, enhancements in specialized training, promotion of evidence-based practices, and integration of technology. We also emphasize the need for stronger policy support and increased funding to improve the neonatal care infrastructure. By adopting these recommendations, India can make significant strides towards improving neonatal outcomes and aligning itself with global health targets.